A systematic review with meta-analysis on the efficacy of 0.01% atropine eyedrops in preventing myopia progression in worldwide children’s populations - Navarra, Pierluigi; Buzzonetti, Luca; Amico, Valentina; Cro, Melina; Federico, Bruno (Frontiers in Pharmacology, 2025)
IntroductionAtropine eyedrops have long been used off-label to prevent myopia progression in children, and many clinical trials have been published on this topic in the past 30 years. Trials initially tested doses ranging from 0.01% to 1%, but more recently, the interest has turned to low doses, mainly 0.01%. Moreover, the first studies were carried out in Asian populations, but the number of trials conducted in other geographical areas has rapidly increased from 2020 onward. This meta-analysis was aimed at summarizing the evidence on the efficacy of 0.01% atropine eyedrops on the reduction of myopia progression, also comparing study findings from different parts of the world.MethodsData were obtained from PubMed, Scopus and Web of Science databases from 1 January 1 2020 to 31 July 2024. Randomized controlled trials involving children receiving 0.01% atropine eyedrops for at least 1 year were included. Heterogeneity was quantified by Q, H, and I2 statistics, and a meta-analysis was performed using a random effect model. The risk for bias was assessed using the Cochrane Collaboration (Chapter 6) aspects of bias scale.Results and discussionThe primary outcomes were the differences in spherical equivalent refractive errors and axial length at baseline and after 12 months of treatment with 0.01% atropine eyedrops or placebo. Eleven studies involving 2,046 children (1,172 receiving 0.01% atropine eyedrops and 874 receiving placebo) were included. Atropine was significantly more effective than placebo, with an average reduction of 0.16/year (95% CI: 0.11–0.22) and −0.07/year (95% CI: −0.09 to −0.05) in spherical equivalent refractive errors and axial length, respectively. The efficacy of 0.01% atropine eyedrops vs. placebo was maintained in a subpopulation of subjects after 24 months of treatment. We found no difference in atropine efficacy between Southeast Asian populations (1,063 children, 52%) and populations in various other countries (983 children, 48%).